Planejamento urbano e geração de empregos: A cidade de São Paulo (Brasil) nos anos 90 - Oliveira, Alberto de [UNESP] (Pontificia Universidad Catolica de Chile, 2005)
This paper attempts to show the convergence of principles between labor market politics and urban management, emphasizing it relationship with pro-market theories. Limits and possibilities of the application of this theoretical frame were investigated by examining the changes in both composition and stock of labor in three important business spaces in São Paulo: Central Area, Paulista Avenue and the new expansion front near Luiz Carlos Berrini and Águas Epraiadas avenues. Despite the claims of pro-market theoreticians, information provided by Labor Ministry showed that between 1996 and 2000, a re-arrangemenet of the workers contingent among the investigated areas occurred, instead of the expected growth. The favorable behavior registered in Berrini/ Águas Espraiadas, because of the bulky volume of investments, took place at the same time that a decrease of labor in the Downtown; meanwhile, in Paulista, a growth of the number of employees was observed, in spite of the landing less elevated of investments.
Urban planning and labor generation: The city of São Paulo (Brasil) in the ninetees
Keywords: Labor market; São Paulo; Urban planning; labor market; urban planning; Brazil; Sao Paulo [Brazil]; South America; Western Hemisphere; World